In vitro assays for the determination of aminoacyl-tRNA synthetase editing activity - Splan, Kathryn E. (2008)
Aminoacyl-tRNA synthetases are essential enzymes that help to ensure the fidelity of protein translation by accurately aminoacylating (or “charging”) specific tRNA substrates with cognate amino acids. Many synthetases have an additional catalytic activity to confer amino acid editing or proofreading. This activity relieves ambiguities during translation of the genetic code that result from one synthetase activating multiple amino acid substrates. In this review, we describe methods that have been developed for assaying both pre- and post-transfer editing activities. Pre-transfer editing is defined as hydrolysis of a misactivated aminoacyl-adenylate prior to transfer to the tRNA. This reaction has been reported to occur either in the aminoacylation active site or in a separate editing domain. Post-transfer editing refers to the hydrolysis reaction that cleaves the aminoacyl-ester linkage formed between the carbonyl carbon of the amino acid and the 2′ or 3′ hydroxyl group of the ribose on the terminal adenosine. Post-transfer editing takes place in a hydrolytic active site that is distinct from the site of amino acid activation. Here, we focus on methods for determination of steady-state reaction rates using editing assays developed for both classes of synthetases.